The influence of chemical composition on the heat resistance of casted structural steel - Y.G. Aftandiliants (Металознавство та обробка металів, 2021)
The paper presents the results of the study of the influence of chemical composition, temperature, stress and operating time on the creep and durability of structural steels. It is shown that the efficiency of structural steels in conditions of elevated temperatures and loads depends on the chemical composition, stress level, operating time and temperature. The influence of alloying elements is associated with the inhibition of the process of weakening of heat-resistant steels due to the reduction of their diffusion mobility and intensity of redistribution between the ferrite and secondary phases, their coagulation and reduction of structural defects. Mathematical models of relative elongation and fracture time in the process of creep from operating conditions and degree of alloying of steel are constructed. It is established that the efficiency of heat-resistant structural steels depends on 61 - 64% of the degree of alloying, 18 - 21% - the value of external stress, 7 - 18% - temperature and 11% of operating time. It is shown that the coagulation of carbides and nitrides in steels doped with nitrogen and vanadium is slower than carbides in steels doped with molybdenum, which more effectively shifts the softening process of heat-resistant steel in the region of higher temperatures and time.